A novel recycling way of blast furnace dust from steelworks: Electrocoagulation coupled micro-electrolysis system in indigo wastewater treatment. (June 2023) - Guo, Jiaran; Zhang, Yang; Wen, Haitao; Jia, Hui; Wang, Jie
Abstract: In this study, a novel electrocoagulation electrode, based on blast furnace dust (BFD) from steelworks waste, was prepared for indigo wastewater treatment, and the performance was compared with different ratios of Fe–C composite electrodes. The BFD electrode exhibited great electrochemical performance and removal effect. The presence of Fe–C micro-electrolysis in the electrocoagulation system of the BFD electrode was demonstrated by FT-IR, Raman, ESR, and quenching experiments. Density Functional Theory (DFT) calculations further demonstrated that the iron-carbon ratio could influence the degree of O–O breaking and enhance ·OH generation. Finally, the BFD electrode's operating parameters were perfected, and the COD removal and decolorization could reach 75.7% and 95.8% within 60 min, respectively. Fe–C composite electrodes reduce energy consumption compared with the traditional Fe/Al electrode and have a lower production cost, which provides a potential way to recycle and reuse the resources of solid waste in steelworks, the concept of "waste controlled by waste" is realized. Graphical abstract: Image 1 Highlights: The blast furnace dust can be used to prepare Fe–C composite electrodes for the treatment of wastewater. Compared with iron electrodes, BFD electrodes exerted better oxidation and less sludge production. The electrode was stable and effective in both intermittent and continuous modes.